ARISU’S PERSONALITY DEVELOPMENT ACROSS THE DEATH GAMES IN 'ALICE IN BORDERLAND' - Rista Fathika Anggrela; Faya Fadella Jasmine Budiman; Salsabila Dwi Febriyanti (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
This study aimed to find the personality development of the main character in Alice in Borderland TV series, Ryohei Arisu. This research objective can further be detailed into explaining Arisu’s experiences that affect his personality, analyzing Arisu’s specific goals which lead his personality to develop, explaining how Arisu’s personality develops from the beginning until the end of the series, and showing how Arisu's personality development changes after he is transported to the Borderland. Hurlock’s (1974) Theory of Personality Development was used to find out how and why Arisu's personality develops and changes. According to the theory, there are several conditions that are responsible for a personality change, e.g.: changes in the environment, changes in social pressure, and changes in self-concept. The result of the analysis shows that Arisu's selfish, lazy, unconfident, and physically weak personality develops into confident, witty, reflexive, and incredibly responsive characters. Aside from that, Arisu also has a new sense of determination by which he wants to live his life to the fullest and carries on his friends.